Prospek Pembiayaan Syariah untuk Sektor Pertanian - nFN Ashari; nFN Saptana (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2005)
EnglishOne of the main problems in agricultural development is the weakness of capital support. The government have tried to overcome this problem by launching some credit programs for the agricultural sector. Many credit programs, those use fixed interest base, showed less satisfied result. In any cases even generate new problems such as the the greater farmer’s debt and also nonperformance credit. Based on that phenomena it is required the alternative financing schemes. Sharia scheme, can be choosen as the alternative financing model for supporting agricultural development. Different to the conventional credit, the sharia scheme is free of interest, profit loss sharing equity principle, and profit sharing will be executed in the end of transaction. This paper aim at introducing the sharia financing model and its prospect to be implemented in agricultural sectors. The result of study indicate that sharia scheme is prospective to strengthen the capital of agricultural sector. To support implementation of sharia finance in agricultural sector, the crucial factors are political will of policy maker and also intensive socialization related to sharia principle finance to public authority and society. IndonesianSalah satu permasalahan utama dalam pembangunan di sektor pertanian adalah lemahnya permodalan. Pemerintah telah berusaha mengatasi permasalahan tersebut dengan meluncurkan beberapa kredit program untuk sektor pertanian. Kredit program yang memakai sistem bunga menunjukkan hasil yang kurang memuaskan, bahkan menimbulkan permasalahan baru seperti membengkaknya hutang petani serta kredit macet. Berdasarkan hal tersebut perlu dicari model pembiayaan alternatif, salah satu di antaranya adalah dengan skim syariah. Berbeda dengan model kredit, pembiayaan syariah ini bebas bunga, pembagian keuntungan didasarkan atas bagi hasil yang dilakukan setelah periode transaksi berakhir. Tulisan ini bertujuan untuk menge-nalkan model pembiayaan syariah serta prospek implementasinya di sektor pertanian. Hasil kajian menunjukkan bahwa pembiayaan syariah cukup prospektif untuk memperkuat permodalan di sektor pertanian. Untuk mendu-kung implementasinya di sektor pertanian diperlukan keberpihakan para pembuat kebijakan serta sosialisasi yang intensif mengenai prinsip-prinsip pembiayaan syariah.